Breast Cancer and Anesthesia - Raigon-Ponferrada, Aida; Recio, Maria E.D.; Guerrero-Orriach, Jose L.; Malo-Manso, Alfredo; Escalona-Belmonte, Juan J.; Aliaga, Marta R.; Fernández, Alicia R.; García, Francisco J.F.; Conejo, Emilio A.; Cruz-Mañas, José (Current Pharmaceutical Design, 2019)
Breast cancer is a complex heterogeneous disease that is categorized into several histological and genomic subtypes with relevant prognostic and therapeutical implications. Such diversity requires a multidisciplinary approach for a comprehensive treatment that will involve surgeons, radiotherapists and medical oncologists. Breast cancer is classified as either local (or locoregional), which stands for 90-95% of cases, or metastatic, representing 5% of cases. The management of breast cancer will be determined by the stage of the disease. The treatment of local breast cancer is based on surgery and/or radiotherapy. Systemic breast cancer requires chemotherapy and/or endocrine and/or biological therapy.
Keywords: propofol